Pendampingan Pembuatan Pakan Alternatif Pasta Apung Berbasis Potensi Lokal di Pokdakan PAKWALI, Desa Bakalan, Kecamatan Purwosari, Kabupaten Pasuruan: Assistance in Making Alternative Floating Paste Feed Based on Local Potential in the PAKWALI Fish Farming Group, Bakalan Village, Purwosari District, Pasuruan Regency - Hertika, Asus Maizar Suryanto; Nurlaelih, Euis Elih; Putra, Renanda Baghaz Dzulhamdhani Surya; Alfarisi, Muhammad Asnin; Aisyah, Jumrotul; Rahmadia, Alvira Rizqi; Prananda, Nauval Rifqi; Yudhistira, Ikmal Fahmi (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
The aquaculture sector plays an important role in supporting food security and improving the community's economy. Aquaculture, especially in rural areas, has become one of the main pillars in providing protein sources for the community and also driving the local economy. This community service activity aims to improve the skills and independence of fish farmers in the Fish Farmers Group (PAKWALI) of Bakalan Village, Pasuruan Regency through the innovation of alternative floating paste feed based on local potential. The main problems faced by partners are the high cost of commercial feed and the lack of knowledge about making independent feed. The methods used include counseling, training, and assistance in making alternative feed. The main innovation is the development of floating paste feed that uses local raw materials such as tofu dregs and bran. The results of the activity showed an increase in the skills of partners in producing independent feed, with production cost efficiency reaching 40.3% compared to commercial feed. This alternative feed also increases the efficiency of nutrient absorption in fish and reduces feed waste. In conclusion, this program has succeeded in increasing the independence of fish farmers, reducing production costs, and encouraging more environmentally friendly and sustainable cultivation practices.